Fodder value of Sudan grass depending on the harvesting time - A. V. Alabushev; N. A. Kovtunova; V. V. Kovtunov; G. M. Ermolina (Аграрная наука Евро-Северо-Востока, 2019)
Among scientists there has been no agreement on which vegetation phase is the most suitable for harvesting of green mass of Sudan grass to provide the largest yield of highly qualitative forage. It has largely depended on the characteristics of the region, varietal composition and, therefore, these studies have been of great value and relevance. The purpose of the study is to identify the optimal time for harvesting green mass of Sudan grass to ensure maximum fodder value. The studies were conducted in 2015-2018 in the conditions of the Rostov region. The Sudan grass variety ‘Aleksandrina’ was used as an object of the study. The analysis of plant height changes through the vegetative phases has shown that there was the largest increase in plant height per day during the period ‘the 30-th day – booting stage’ (7.18 cm) and ‘booting stage – heading stage’ (5.83 cm). Plant growth after flowering stopped and the increase of the yield of green mass was only due to lateral stems. The structural analysis has shown that the largest part of the green mass of Sudan grass was represented by the stem (58-61%). The proportion of leaves, considered to be the most nutritious parts of plants, decreased from 35% (‘the booting stage’) to 20% (‘milky ripening of grain’) as the plants were growing. The productivity of green mass of Sudan grass was largely determined by the first hay cutting (59-63% of the total). The green mass of the second hay cutting corresponded to the amount of digestible protein per one fodder unit (113.7-128.9 g) and produced maximum yield when harvesting in the ‘heading stage’. Though the green mass productivity increased in the period from ‘booting stage’ to ‘flowering’, the content of raw protein reduced from 10.45 to 7.96%. This resulted in a decrease of digestible protein percentage per one fodder unit. Thus, the data on yield and quality of green mass of Sudan grass ‘Aleksandrina’ have shown that the harvesting could be already started in the ‘booting stage’, however, the highest nutritional value has been identified in the early ‘heading stage’.